Distinct Antiretroviral Mechanisms Elicited by a Viral Mutagen. Issue 18 (3rd September 2021) - Roth, Megan; McDaniel, Yumeng Z.; Daly, Michele B.; Talledge, Nathaniel; Greggs, Willie M.; Patterson, Steven E.; Kim, Baek; Mansky, Louis M.
Graphical abstract: Highlights: 5-aza-C has previously been shown to be a HIV-1 mutagen. Comparative analysis of 5-aza-C was done between HIV-1 and MuLV. 5-aza-C did not significantly increase the mutational burden in MuLV. A viral mutagen can have potent activity against related viruses via distinct mechanisms. Abstract: 5-aza-cytidine (5-aza-C) has been shown to be a potent human immunodeficiency virus type 1 (HIV-1) mutagen that induces G-to-C hypermutagenesis by incorporation of the reduced form (i.e ., 5-aza-dC, 5-aza-dCTP). Evidence to date suggests that this lethal mutagenesis is the primary antiretroviral mechanism for 5-aza-C. To investigate the breadth of application of 5-aza-C as an antiretroviral mutagen, we have conducted a comparative, parallel analysis of the antiviral mechanism of 5-aza-C between HIV-1 and gammaretroviruses – i.e ., murine leukemia virus (MuLV) and feline leukemia virus (FeLV). Intriguingly, in contrast to the hallmark G-to-C hypermutagenesis observed with HIV-1, MuLV and FeLV did not reveal the presence of a significant increase in mutational burden, particularly that of G-to-C transversion mutations. The effect of 5-aza-dCTP on DNA synthesis revealed that while HIV-1 RT was not inhibited by 5-aza-dCTP even at 100 µM, 5-aza-dCTP was incorporated and significantly inhibited MuLV RT, generating pause sites and reducing the fully extended product. 5-aza-dCTP was found to be incorporated into DNA by MuLV RT or HIV-1 RT, but only acted as a non-obligate chain terminator for MuLV RT. This biochemical data provides an independent line of experimental evidence in support of the conclusion that HIV-1 and MuLV have distinct primary mechanisms of antiretroviral action with 5-aza-C. Taken together, our data provides striking evidence that an antiretroviral mutagen can have strong potency via distinct mechanisms of action among closely related viruses, unlinking antiviral activity from antiviral mechanism of action.